The addition of etoposide to CHOP is associated with improved outcome in ALK+ adult anaplastic large cell lymphoma: A Nordic Lymphoma Group study. (8th May 2017) - Cederleuf, Henrik; Bjerregård Pedersen, Martin; Jerkeman, Mats; Relander, Thomas; d'Amore, Francesco; Ellin, Fredrik
Summary: Anaplastic large cell lymphomas (ALCLs) are rare CD30+ peripheral T‐cell lymphomas (PTCLs) classified according to the expression of the anaplastic lymphoma kinase (ALK+) protein or not (ALK−). We have analysed the outcome and risk factors for survival in a population‐based bi‐national cohort of patients with systemic ALK+ ALCL. A total of 122 adult (≥18 years) patients diagnosed with ALK+ ALCL between 2000 and 2010 were identified from the Danish and Swedish lymphoma registries, representing 0·4% of all lymphomas. The median age of the cohort was 40 years (range 18–85). The 5‐year overall survival and progression‐free survival (PFS) was 78% and 64%, respectively. Age was strongly associated with outcome, and only bone marrow (BM) involvement was independently associated with poorer PFS in multivariate analysis (Hazard Ratio [HR] = 8·57, P < 0·001). Age stratification of the patients demonstrated an association between treatment with CHOEP (cyclophosphamide, doxorubicin, vincristine, etoposide, prednisolone) and improved overall survival for patients aged 41–65 years, even when adjusted for risk factors (HR = 0·38, P = 0·047). Our results suggest that the addition of etoposide to CHOP (cyclophosphamide, doxorubicin, vincristine, prednisolone) in the treatment for ALK+ ALCL seems reasonable in this age group.